Conceptual framework development to explore the service experience in customer care centre of Telecom industry in Kota Kinabalu, Sabah, Malaysia - Iftekhar Amin Chowdhury; Joehan Joehari William; Norazah Mohd Suki (International Journal of Asian Academic Research Associates, 2015)
Customer care centres have become a major business field over the past few years. Efficiency and service excellence are the two major goals for customer care centre. Efficiency depends on speed and delivery that leads to get excellent service. The objectives of the research is to identify and explore the influential factors of the service experience in customer care centre in Malaysia. The research will identify the critical factors of service experience of customer care centre to eliminate the rigidity of service near future. Questionnaire survey is appropriate for this research because the research method is quantitative and experimental. Data will be collected from the people who are attached with the customer care centre activities in terms of usage of the product or seeking services through customer care centre. Before that in this theoretical paper, it tried to analyse the three theories that is to comprehend the factors influencing the customer’s service experience in a modern customer care centre in Kota Kinabalu, Sabah, Malaysia. Results of this study will show that how different factors influence and shape a better service experience and whether the factors will have positive and significant influences on customer’s service experience in a customer care centre in Malaysia. The service marketing mix, the servuction framework and the services theatre framework are the major theories that will explain and discuss the service experience in this research to determine the outcome later on.